2023
DOI: 10.21037/atm-22-6120
|View full text |Cite
|
Sign up to set email alerts
|

ncRNA-mediated low expression of P2RY14 correlates with poor prognosis and tumor immune infiltration in ovarian carcinoma

Abstract: Background: Ovarian cancer (OV) has been puzzling clinicians because of its poor prognosis. More and more evidence show that the G protein coupled receptor P2RY14 plays a key role in the initiation and progression of various types of human cancer. The purpose of our study is to explore the correlation between P2RY14 and the prognosis of ovarian cancer patients and the relevant mechanism.Methods: First, the differentially expressed gene P2RY14 was screened from The Cancer Genome Atlas (TCGA) database. Explored … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…7 Evidence confirmed that P2RY14 may be involved in LUAD immune invasion and inhibit tumor cell immune 下Áescape within LUAD microenvironment. 8 A significant impact of JAML expression on LUAD prognosis and TME was observed, which highlights the importance of TME on LUAD patients. 9 Novel biomarkers related to TME in the OS of LUAD patients are urgently needed for predicting clinical management.…”
mentioning
confidence: 83%
See 1 more Smart Citation
“…7 Evidence confirmed that P2RY14 may be involved in LUAD immune invasion and inhibit tumor cell immune 下Áescape within LUAD microenvironment. 8 A significant impact of JAML expression on LUAD prognosis and TME was observed, which highlights the importance of TME on LUAD patients. 9 Novel biomarkers related to TME in the OS of LUAD patients are urgently needed for predicting clinical management.…”
mentioning
confidence: 83%
“…It performs an integral function in LUAD progression with significant heterogeneity 7 . Evidence confirmed that P2RY14 may be involved in LUAD immune invasion and inhibit tumor cell immune 下·escape within LUAD microenvironment 8 . A significant impact of JAML expression on LUAD prognosis and TME was observed, which highlights the importance of TME on LUAD patients 9 .…”
Section: Introductionmentioning
confidence: 89%
“…Interestingly, lncRNA LINC00665 acts as a sponge for miR-34c-5p, preventing its interaction with P2RY14. This leads to the maintenance of low P2RY14 expression, which, in turn, correlates with poor prognosis and increased tumor immune infiltration in ovarian carcinoma [80]. The dysregulation of miR-34 family members and their downstream targets in ovarian cancer provides valuable insights into their significant roles in disease progression.…”
Section: The Tumor-suppressive Effects Of Mir-34s In Ovarian Cancermentioning
confidence: 99%